(untitled) (Research, Society and Development, 2021)
Biotechnological processes with microalgae with the aim to achieve high biomass yields must choose the appropriate nutrients and physicochemical parameters, taking into account the specific characteristics of each species to determine the basic needs for its growth. In the present study, the better growth condition of Chlorella sorokiniana IPR 7104 was optimized to reach the maximum beta-galactosidase production. The cheese whey concentration (%), temperature (˚C) and pH were factors investigated and a Box-Behnken Design (BBD) approach was implemented using Statistica 7.0 software. We observed that the cultivation condition to Chlorella sorokiniana IPR 7104 was the heterotrophic, which showed the major enzymatic activity, consequently a lower residual lactose content. Under heterotrophic conditions (without light) the β-galactosidase activity increased linearly until the 8th day. Biomass production grew linearly on the 12th day. The microalgae consumed 89.6% of lactose in 3 days, showing a high capacity to metabolize this disaccharide, through β-galactosidase synthesis. The maximum β-galactosidase production by Chlorella sorokiniana IPR 7104, in heterotrophic conditions and using cheese whey as carbon source, is obtained using the following conditions: 30°C temperature, concentration of ethanol at 20% and time of 4 min.